Attention Allocation to Financial Information: The Role of Color and Impulsivity Personality Trait - Ceravolo, Maria G.; Cerroni, Rocco; Farina, Vincenzo; Fattobene, Lucrezia; Leonelli, Lucia; Mercuri, Nicola B.; Raggetti, GianMario (Frontiers in Neuroscience, 2019)
Background. In order to raise the level of investor’s protection, the European Commission has recently introduced the Key Investor Information Document (KIID), a standard, plainly worded, consumer-friendly document which should provide individuals with essential information for their investment decisions. KIID layout has been delineated relying on results from focus groups, surveys and telephone interviews, ignoring the reliable and unbiased insights offered by neuroscientific approaches. Aim. The current study aims to elucidate the patterns of eye movements in the early phases of information acquisition during the reading of financial disclosure documents, disentangling the independent role of information color and impulsivity at modulating attention distribution towards the different sources of financial information. Materials and Methods. Oculomotor behavior was monitored in eighty-one healthy adults through the eye tracking technology (SMI REDn Scientific 60Hz). An ecological protocol exploiting official KIIDs was developed to control for several individual variables, through delivering standard visual stimuli based on official financial documents. Participants performed a passive exploration task (with the only specific instruction of visually exploring the document), followed by an active task where they were asked to rate the financial attractiveness of the products, as low, medium or high. The Barratt impulsiveness scale (BIS-11) was administered to each participant, to score such personality trait. Results. Attention distribution over the different information sources, included in the KIIDs, has been quantified and found to be independently modulated by both color and impulsivity, with a greater role of the former over the latter. The addition of either red or blue information to some KIID’s sections increases attention allocation towards the whole document, compared to the usual black and white version. BIS-11 total scores were inversely related to the first and average fixation duration in the neutral, though not in the colored condition. Discussion. Bottom-up, stimulus-related mechanisms of attention allocation influence information acquisition during the reading of financial prospectuses to the point that the increased attention induced by color compensates for individual impulsivity. Such evidence should be considered by regulators when devising the disclosure documents in order to increase investors’ protection.